Comparative analysis of ammonia monooxygenase (amoA) genes in the water column and sediment–water interface of two lakes and the Baltic Sea - Ok-Sun, Kim; Junier, Pilar; Imhoff, Johannes F; Witzel, Karl-Paul (My University, 2008)
The functional gene amoA was used to compare the diversity of ammonia-oxidizing bacteria (AOB) in the water column and sediment–water interface of the two freshwater lakes Plußsee and Schöhsee and the Baltic Sea. Nested amplifications were used to increase the sensitivity of amoA detection, and to amplify a 789-bp fragment from which clone libraries were prepared. The larger part of the sequences was only distantly related to any of the cultured AOB and is considered to represent new clusters of AOB within the Nitrosomonas/Nitrosospira group. Almost all sequences from the water column of the Baltic Sea and from 1-m depth of Schöhsee were related to different Nitrosospira clusters 0 and 2, respectively. The majority of sequences from Plußsee and Schöhsee were associated with sequences from Chesapeake Bay, from a previous study of Plußsee and from rice roots in Nitrosospira -like cluster A, which lacks sequences from Baltic Sea. Two groups of sequences from Baltic Sea sediment were related to clonal sequences from other brackish/marine habitats in the purely environmental Nitrosospira-like cluster B and the Nitrosomonas-like cluster. This confirms previous results from 16S rRNA gene libraries that indicated the existence of hitherto uncultivated AOB in lake and Baltic Sea samples, and showed a differential distribution of AOB along the water column and sediment of these environments.
Keywords: amoA; ammonia-oxidizing bacteria; Plußsee; Schoehsee; Baltic Sea